The Efforts of Sawahlunto MSMEs in Preserving Batik as A Symbol of Beauty, Philosophy, And National Identity - Ferdian, Agung; Salsabilla, Fara Diva; Putra, Hendro Riza; Primawardani, Natasya Calesta; Zelvy, Nurul Fatimah; Sari, Anggun Permata (Abdimas Indonesian Journal, 2025)
This study aims to comprehensively analyze the strategic role of Micro, Small, and Medium Enterprises (MSMEs) in Sawahlunto City in preserving Sawahlunto Charcoal Batik, a cultural product born from the innovation and mining history of this ancient city. Charcoal Batik is positioned not merely as a creative economic commodity, but as a medium for cultural inheritance rich in symbols of beauty, local philosophy, and national identity. Using descriptive qualitative methods, this study outlines the role of MSMEs as producers of identity, guardians of philosophy, and agents of skills regeneration. Key findings indicate that MSMEs, supported by government intervention and empowerment programs such as the Community Service Program (KKN), have successfully transformed the dark history of mining into a proud cultural heritage. The success of MSMEs in preserving motifs inspired by the Ombilin Sawahlunto Coal Mining Heritage (WTBOS) emphasizes their crucial role as pillars of cultural-economic preservation, significantly improving welfare while maintaining local identity.